Portrayal of Women in Women's Magazine Advertisements Comparison Between Her World and Wanita - Kalaiyarasi, Kathlraveloo (2001)
Gender stereotyping is one of the dilemma that still exists and is prevalent in the advertising industry in Malaysia. Advertisements tend to represent women in limited' roles. Advertisements generally depict women as homemakers or mothers or show them as sex objects or sexually provocative figures. Seldom women are shown in work settings, business roles, or in position of responsibility and authority. Since women are always portrayed as decorative objects by media, women's magazines should take the lead to prevent this culture from being practiced continuously. The overall objective of this study is to do a comparison between Her World and Wanita advertisements on the portrayal of women for the year 1997. Data was collected using content analysis. They were 184 advertisements in Wanita magazine and 344 advertisements in Her World magazine. Descriptive statistics and chi-square test were used to analyze the data. The result showed that, most of the advertisements in Her World and Wanita were in bleed pages and in full color, placed at the upper half of the magazine. The result also indicated that advertisers preferred general settings with at least one female portrayal to promote their product. Both magazines were very keen in portraying women in characterization stereotypical positions. Besides this, casual wear was the most frequently used attire in both Her World and Wanita advertisements. Both magazine also emphasized more on emotional appeals to gain attention of the readers. In terms of advertising execution, both magazines preferred factual message to place their women portrayal advertisements. The results also indicated that Her World advertisements emphasized more on personal care products whereas Wanita advertisements focused more on cosmetics advertisements. The Chi-square test results indicated that there were significant differences in the portrayal of women between Her World and Wanita in terms of advertisements placement, color of the advertisement, role of women portrayal, advertising execution, types of attire and also the types of product. Overall, this study revealed that advertisers, especially in women's magazines do more damage to the portrayal of women by placing them in inaccurate positions. Women portrayal is mainly used to gain attention of the readers. Most of the time, the presence of pretty women has no relevance to the quality of the product that is being advertised. Advertisers also use women as sex symbols to gain attention of the readers. Since women magazine advertisements had failed to acknowledge the current status of women, there should be more research, talk, seminars, and guidelines to tackle this issue.